Karakter Root Re-Growth Sebagai Parameter Toleransi Aluminium pada Tanaman Padi - Roslim, Dewi Indriyani; Miftahudin, Miftahudin; Suharsono, Utut; Aswidinnoor, Hajrial; Hartana, Alex (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2010)
Aluminum (Al) is one of the major limited factors in crop production on acid soils. Aluminum tolerant plants can beselected from plant breeding program by one of the physiological parameters representing Al tolerance character,such as root re-growth capability during recovery from the Al-stress. In this study we determined the concentrationand time exposure of Al stress that was able to differentiate the response of three local upland rice varieties(Grogol, Hawarabunar and Krowal) and an Al-sensitive rice variety (IR64) to Al-stress, and evaluated the effectivenessof root re-growth (RRG) characters as an Al tolerance parameter in rice. The study consisted of three experiments,which were 1) nutrient culture experiment with different Al concentration treatments in growth chamber, 2) potexperiment in greenhouse using Jasinga yellow red podzolic acid soil containing 26,66 me/100 g Al and pH 4,6 asplanting media, and 3) phenotyping of F2 population using RRG character. The results showed that Al treatment at15 ppm for 72 h was able to distinctly differentiate between Al-tolerant (Grogol and Hawarabunar) and Al-sensitivevarieties (Krowal and IR64). Planting of the rice varieties on acid soils showed similar result as that of the nutrientculture. Phenotyping of F2 population using RRG character indicated the existence of RRG value variation. Thesevariations demonstrated that RRG character can be used as an Al tolerance parameter in rice and therefore can beeffectively applied to screen rice F2 population that segregate to Al tolerance character.